Comparison of Postpartum Urinary Retention Healing between Groups with Methods of Residual Urine Measurement Four Hours versus Six Hours Post-Delivery: Perbandingan Lama Pemulihan Retensio Urin Pascapersalinan Pervaginam antara Pengukuran Residu Urin Empat dan Enam Jam - Fernandi Moegni; Ummu Hani (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: To know the difference of recovery time and the urinary residual volume between group of patient with different time of urinary residual collecting. Method: A randomized controlled trial was held at Dr. Cipto Mangunkusumo central general hospital and central Karawang hospital between March and Desember 2017. Postpartum women with urinary retention risks, willing to contribute to the trial, and diagnosed as post partum urinary retention were divided into 2 groups. Urinary residual volume was measured in 4th hour and 6th hour in each group. Patient then treated according to RSCM guideline, and the time of recovery was documented. Result: Both group have similar characteristic. The median length of recovery in the group which the urinary residual was measured in 4th hour was 30 hours, 21 hours shorter than 6th hour group, 51 hours (p< 0.001). The median of urinary residual volume of the 4th hour group was 600 ml, 400 ml lesser than the 6th hour group, 1000 ml (p< 0.001) Conclussion: time of recovery are shorter in the 4th hour group and the urinary residual volume are less in the 4th hour group compared to the 6th hour group. Keywords: post partum urinary retention, urine residual, urinary residual collecting time Abstrak Tujuan: untuk mengetahui lama pemulihan dan volume residu urin pada kelompok pasien dengan retensio urin pascapersalinan dengan beda waktu pengukuran, Metode: Penelitian ini menggunakan desai uji klinis acak di RSUPN Dr. Cipto Mangunkusumo dan RSUD Karawang bulan Maret-Desember 2017. Perermpuan pascasalin dengan risiko retensio urin pasca persalinan, bersedia mengikuti penelitian, dan terdiagnosis retensio urin dibagi menjadi dua kelompok. Kelompok pertama diukur residu urinnya dalam 4 jam, kelompok kedua dalam 6 jam. Pasien lalu diberikan tatalaksana retensio urin sesuai protokol RSUPNCM dan dicatat waktu pulihnya. Hasil: Karakteristik pasien pada kedua kelompok dianggap setara. Median lama pemulihan pasien retensio urin yang diukur residu urin 4 jam adalah 30 jam, berbeda 21 jam dengan pasien yang diukur resiudnya 6 jam, yaitu 51 jam (p<0.001). Median jumlah residu urin pada kelompok pengukuran residu urin 4 jam adalah 600 ml, berbeda 400 ml dengan kelompok pengukuran 6 jam, yaitu 1.000 ml (p<0.001). Kesimpulan: Lama pemulihan lebih singkat pada kelompok pasien dengan waktu pengukuran residu urin 4 jam dibandingkan dengan 6 jam. Jumlah residu urin lebih sedikit pada pengukuran residu 4 jam dibanding 6 jam Kata kunci: retensio urin pasca persalinan, residu urin, waktu pengukuran residu urin